A CRITICAL REVIEW OF IBNU KHALDUN'S PHILOSOPHY OF EDUCATION IN THE PERSPECTIVE OF 21ST CENTURY EDUCATION - Wahyu Sihab; Husnaini, M (Joyful Learning Journal, 2025)
This study aims to critically examine Ibn Khaldun's philosophy of education in the perspective of the challenges and needs of 21st century education. Ibn Khaldun viewed education as a gradual process that is not only oriented towards intellectual achievement, but also character building and social awareness. Using the systematic literature review (SLR) method, this study analyzes many sources, both classical and contemporary, to understand and identify the relevance of Ibn Khaldun's thoughts to contemporary educational principles, such as experiential learning, contextual curriculum, and the role of educators as moral coaches. The results of the study show that Ibn Khaldun's educational concepts are in line with the transformative approach in modern education that emphasizes the balance between knowledge, skills, and values. The actualization of his thoughts can make an important contribution in designing an education system that is more adaptive, humanistic, and oriented to the benefit of the people. The findings provide a strong philosophical basis for curriculum development and contextualized pedagogical practices in the global era.